Association between nutritional status and severity of RSV-associated lower respiratory tract infection: a retrospective study in hospitalised children under 5 years of age - Jittima Monwiratkul; Kornthip Jeephet; Klaita Srisingh (BMJ Nutrition, Prevention & Health)
Introduction Severe lower respiratory tract infection (LRTI) caused by respiratory syncytial virus (RSV) is a major cause of respiratory morbidity in children. Nutritional status is hypothesised to influence the severity of RSV infection, affecting clinical outcomes.Objective To evaluate the association between malnutrition and the severity of RSV-related LRTI in children.Methods A retrospective study was conducted at Naresuan University Hospital, including children under 5 years of age diagnosed with RSV LRTI between January 2014 and December 2018. Nutritional status was assessed using Z-scores for wasting (weight-for-height), underweight (weight-for-age), stunting (height-for-age) and both undernutrition and overnutrition (body mass index). Data were analysed using STATA V.18. Univariate analysis used t-test and χ2 test. Variables with p<0.2 entered multivariate logistic regression to identify risk factors. Adjusted ORs (aORs) with 95% CI were reported; p<0.05 was significant.Results A total of 250 children met the inclusion criteria, with 36 (14.4%) classified as having severe RSV LRTI and 214 (85.6%) as non-severe cases. Among those with severe RSV-related LRTI, 16 (44.4%) were male and 20 (55.6%) were female, whereas in the non-severe group, 119 (55.6%) were male and 95 (44.4%) were female. Multivariable analysis revealed that severe wasting (aOR=3.70; 95% CI 1.01 to 13.55; p=0.048) and severe underweight (aOR=9.09; 95% CI 2.62 to 31.50; p=0.001) were strongly correlated with severe RSV LRTI.Discussion Severe wasting and severe underweight are significant risk factors for severe RSV LRTI in children. These findings suggest that improving nutritional status may help reduce the severity of RSV LRTI.